PEDAGOGICAL APPROACHES USED BY TEACHERS IN TEACHING MAPEH IN THE DIVISION OF TUGUEGARAO CITY, PHILIPPINES - CARAG, EDUARDO ACEBO (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to admonish the use of multiple innovative pedagogical approaches that would fit different kinds of students’ abilities. Imbibing to the learners the technologically, globally and collaboratively equipped factors that consider success in teaching – learning process. Effectiveness of these approaches may vary depending on the subjects, strategies and methods used in teaching. In teaching the subject MAPEH, different approaches were employed.This study made use of descriptive-correlation method of investigation to secure adequate and reliable data needed. The utilization innovative strategies for Inquiry Based, Collaborative, Integrative and Constructivist vary from different techniques used in teaching MAPEH is commendable yet need to be more effective.As such, students may use academic concepts on visual and practical learning that may help them understand the real life. Through verbally expressing their ideas and responding to others, your students will be able to develop their self-confidence, as well as enhance their communication and critical thinking skills which are vital throughout life. Students may encourage to use probing questions during discussions that would help them develop critical thinking. As provider of knowledge, teachers in MAPEH may use technology as an innovative tool for improving quality teaching- learning process and may participate in a seminar workshop for them to enhance their teaching capabilities as mentors.